MENGKONSTRUKSI FAKTOR TRUST DALAM TRANSAKSI PENJUALAN SECARA KREDIT (Studi terhadap Tukang Kredit Migran asal Tasikmalaya di Kota Pekanbaru) - Abdul Aziz (UIR Press, 2018)
Itinerant profession mortgagee sells a variety of household appliances, is a typical profession of Tasikmalayapeople. Distinctive feature of this loan among them; do not use the guarantee, does not require a down payment, and very flexible repayment can be done on a daily, weekly, and monthly. In this business, trust is a major factor that is used as a handle mortgagee. Reality thus causing no little credit customers who betrayed and ran away from completing repayment obligations. The purpose of research is to understand and analyze: persep the mortgagee against himself and his profession; mortgagee interpersonal communication process with customers; and konstruksisosial mortgagee about the trust factor against pelanggannya.Untuk achieve these objectives, the study uses a constructivist paradigm and qualitative research methods, the research subjects consisted of 13 people mortgagee selected purposively. The approach used in this study is the symbolic interactionism and teorikonstruksisosialatas reality, and to collect the data used in-depth interviews, participant observation and documentation study. The findings of the research include: view mortgagee against himself and his profession is generally very positive. Interpersonal communication process with customers mortgagee are colored with impression management both verbally and nonverbally. Construction trust to customers much based on nonverbal communication behavior of customers and economic conditions customers.